Kewirausahaan Digital Pada Forum Komunikasi Muslimah Indonesia Di Malaysia (Fokma) - Lesmana, Rosa; Sunarto, Ading; Latif, Latif (LPPM Universitas Pamulang, 2024)
Abstract. The purpose of this community service is to provide additional knowledge to Fokma Muslim women regarding digital entrepreneurship so that they can face developments, challenges, and competition in the era of globalization. The audience is Indonesian Muslim women residing in Malaysia. The methods used include lectures, training, and discussions. Digital entrepreneurship is expected to provide value propositions for superior and differentiated products and services, establish good relationships with suppliers, distributors, and resellers, recognize and build good relationships with customers, comply with legal regulations, seek sources of business capital, and conduct effective and efficient promotions.